1987
DOI: 10.2134/agronj1987.00021962007900050035x
|View full text |Cite
|
Sign up to set email alerts
|

Root Growth, Seedhead Production, and Quality of Annual Bluegrass as Affected by Mefluidide and a Wetting Agent1

Abstract: Annual bluegrass [Poa annua ssp. reptans (Hauskins) Timm.] often comprises a large portion of golf course greens, yet its shallow root system and extensive seedhead production limit its turf quality. The purpose of this investigation was to determine if annual bluegrass seedheads could be suppressed and rooting enhanced by the plant growth regulator mefluidide [N ‐(2,4‐dimethyl‐5‐{[(trifluoromethyl) sulfonyl]amino} phenyl)acetamide] and the wetting agent Aqua‐Gro (polyoxyethylene esters and ether of cyclic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 4 publications
1
34
1
Order By: Relevance
“…Long wave ultra-violet (320± 400 nm) light (Model B-100AaR Blak-Ray Ultra-Violet Lamp, UVP, Inc., San Gabriel, CA) was used to facilitate viewing of actively growing viable roots (16,17,23). Root measurements commenced 12 April 1997 and terminated 25 September 1998, totaling 39 independent observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long wave ultra-violet (320± 400 nm) light (Model B-100AaR Blak-Ray Ultra-Violet Lamp, UVP, Inc., San Gabriel, CA) was used to facilitate viewing of actively growing viable roots (16,17,23). Root measurements commenced 12 April 1997 and terminated 25 September 1998, totaling 39 independent observations.…”
Section: Methodsmentioning
confidence: 99%
“…These inconsistencies, common to bentgrass root research, may in part result from the relationship of root length density (RLD) to shoot density at shallow soil depths. Improvements have been made by reporting bentgrass rootto-shoot ratios (RSR), speci®c root lengths (SRL) (15), and viable root length measurements (16,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Cooper et al (1987) showed an increase in root elongation and rooting depth from applications of mefluidide to annual bluegrass (Poa annua var. reptans (Hausskn.)…”
mentioning
confidence: 99%
“…The highest rate of foliar-applied mefluidide inhibited height growth 2 weeks after application, but mefluidide also caused chlorosis and leaf malformation at the two higher rates. Hanson and Branham (1987) and Cooper et al (1987Cooper et al ( , 1988 obtained seedhead suppression in Poa when mefluidide was applied at 0.28 kg/ha or less, and short-term yellowing of foliage occurred. We found that mefluidide applications of 0.54 kg/ha delayed flowering in Canada thistle for at least 3 weeks with no foliar chlorosis (data not shown).…”
Section: Canada Thistle Growth Following Pgr Application To Foliage Omentioning
confidence: 94%
“…(Cooper et al 1987(Cooper et al , 1988. Similarly, Hanson and Branham (1987) demonstrated that movement of photosynthate to roots of 'Majestic' Kentucky bluegrass (Poa pratensis L.) could be enhanced following applications of mefluidide.…”
mentioning
confidence: 98%